Driving simulators in the clinical assessment of fitness to drive in sleepy individuals: A systematic review. (April 2018) - Schreier, David R.; Banks, Christina; Mathis, Johannes
Summary: Road traffic injuries are projected to be the leading cause of death for those aged between 15 and 29 years by the year 2030, and sleepiness is estimated to be the underlying cause in up to 15–20% of all motor vehicle accidents. Sleepiness at the wheel is most often caused by socially induced sleep deprivation or poor sleep hygiene in otherwise healthy individuals, medical disorders, or the intake of drugs. Validated methods for objectifying sleepiness are urgently sought, particularly in the context of driving. Based on the assumption that the identification and treatment of sleepiness, and its causes, may prevent motor vehicle accidents, driving simulators are a seemingly promising diagnostic tool. Despite the rising use of these in research, the reliability of their conclusions in healthy sleepy individuals and patients is still unclear. This systematic review aims to evaluate the practical value of driving simulators in a clinical environment when judging fitness to drive in sleepy individuals. From the 1674 records screened, 12 studies in sleepy individuals containing both simulated and real driving data were included. In general, simulated driving did not reliably predict real-life motor vehicle accidents, and especially not on an individual level, despite the moderate relationship between simulated and real-road test driving performance. The severity of sleepiness is most likely not the critical factor leading to motor vehicle accidents, but rather the perception of sleepiness. The self-perception of sleepiness related impairment, and risky behaviour while at the wheel should also be considered as key influencing factors.